Capital Expenditure: Antecedents and Its Impact on Economic Growth - Jefri Suryo Winarto; M. G. Kentris Indarti (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to understand how Regional Original Income (PAD), General Allocation Funds (DAU), Special Allocation Funds (DAK), Profit Sharing Funds (DBH), Budget Financing Excess (SILPA), and Area Area influence capital expenditure in the Regency and cities in Central Java during the 2018-2022 period and their impact on economic growth. This research uses a quantitative approach and collects data using the full sample method. The analysis technique used is panel data model testing with the CEM, FEM, and REM approaches. Model selection using model specification tests: Chow test, Hausman test, and Lagrange multiplier test. Followed by the Classic Assumption test and Hypothesis test. The research results show that PAD, DBH, SILPA, and Area Area do not affect Capital Expenditure. DAU and DAK have a positive and significant effect on capital expenditure. Capital Expenditures have a positive and significant effect on Economic Growth. It is hoped that this research can contribute to policy formulation. The government must explore revenue potential to optimize capital expenditure management in improving public facilities and infrastructure and monitor using DAU and DAK to increase economic growth.